2016
DOI: 10.1590/s0004-28032016000300009
|View full text |Cite
|
Sign up to set email alerts
|

IS RESECTION OF HEPATOCELLULAR CARCINOMA IN THE ERA OF LIVER TRANSPLANTATION WORTHWILE? A single center experience

Abstract: - Resection, for selected cases, is a potentially curative treatment with acceptable morbidity and mortality and, in a context of a long waiting list for transplant, plays an important role for the treatment of hepatocellular carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
13

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 47 publications
0
10
0
13
Order By: Relevance
“…Laparoscopic approach for liver resection is gaining space worldwide, especially in the treatment of benign tumors as hepatocellular adenoma 8 , 17 , which is more common in young women, and in the treatment of hepatocellular carcinoma 8 , 18 , with a likely advantage over conventional open approach. According to Kawaguchi et al 21 , the relative number of 30% of minimally invasive approach for all liver resections is the average for specialized centers.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic approach for liver resection is gaining space worldwide, especially in the treatment of benign tumors as hepatocellular adenoma 8 , 17 , which is more common in young women, and in the treatment of hepatocellular carcinoma 8 , 18 , with a likely advantage over conventional open approach. According to Kawaguchi et al 21 , the relative number of 30% of minimally invasive approach for all liver resections is the average for specialized centers.…”
Section: Discussionmentioning
confidence: 99%
“…Hepatocellular carcinoma is a malignancy associated with a high rate of mortality and costs (4) . Hepatocellular carcinoma (HCC) currently, affects 1.5% of the world population and reach approximately 15% of patients on the waiting list for liver transplantation (1,11,21) . Mishra et al (28) has demonstrated that the costs of treating patients with HCC in 2009 were around US$ 31 thousand, with total treatment costs of ap proximately US$ 2 billion in the USA.…”
Section: Introductionmentioning
confidence: 99%
“…As a general rule, 5-year survival rates for patients with HCC after LR are between 50% and 70% and, after LT, between 70% and 80% (138)(139)(140)(141) . The tumor recurrence rate after LR is around 50% and post-LT around 10% (140)(141)(142)(143) . However, considering the long time spent on the waiting list (over 6-9 months), when an intention-totreat analysis is performed, similar survival outcomes are found when comparing LR with LT (137,144) .…”
Section: Surgical Treatmentmentioning
confidence: 95%
“…However, the evolution of surgical techniques and perioperative care has allowed the expansion of liver surgery indications (47) . Thus, limited LR in patients with preserved liver function, small-sized esophageal varices, and platelet counts above 100,000 is feasible in selected patients with "mild" portal hypertension (138,141,146) . Nevertheless, it is noteworthy that even CP A patients can decompensate after major resections (140) .…”
Section: Surgical Treatmentmentioning
confidence: 99%